2003
DOI: 10.1242/dev.00539
|View full text |Cite
|
Sign up to set email alerts
|

Direct and concentration-dependent regulation of the proneural geneNeurogenin2by Pax6

Abstract: Expression of the proneural gene Neurogenin2 is controlled by several enhancer elements, with the E1 element active in restricted progenitor domains in the embryonic spinal cord and telencephalon that express the homeodomain protein Pax6. We show that Pax6 function is both required and sufficient to activate this enhancer, and we identify one evolutionary conserved sequence in the E1 element with high similarity to a consensus Pax6 binding site. This conserved sequence binds Pax6 protein with low affinity both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
196
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(214 citation statements)
references
References 48 publications
12
196
0
4
Order By: Relevance
“…In addition, we confirmed the previous finding that GST-Pax6-PD weakly bound the Ngn2 E1 enhancer element probe E1.1 but not the mutated E1 enhancer probe mtE1.1 (Fig. 8A) (44). Although GST-Pax6-PD could also recognize the 5aCON control probe, GST-Pax6(5a)-PD was unable to bind the P6CON site effectively ( Fig.…”
Section: Stronger Rescue Of Telencephalon Patterning In Pax6supporting
confidence: 90%
See 1 more Smart Citation
“…In addition, we confirmed the previous finding that GST-Pax6-PD weakly bound the Ngn2 E1 enhancer element probe E1.1 but not the mutated E1 enhancer probe mtE1.1 (Fig. 8A) (44). Although GST-Pax6-PD could also recognize the 5aCON control probe, GST-Pax6(5a)-PD was unable to bind the P6CON site effectively ( Fig.…”
Section: Stronger Rescue Of Telencephalon Patterning In Pax6supporting
confidence: 90%
“…Previous studies have shown that the canonical Pax6 isoform through its PD binds to a low affinity site on the Ngn2 E1 enhancer, which promotes Ngn2 expression only in the telencephalic domains of high Pax6 expression (44). To assess whether there could exist a direct physical interaction between the Ngn2 E1 enhancer and Pax6(5a) or Pax2 PD, we performed DNA EMSAs using oligonucleotide probes containing sequences corresponding to the Pax6 binding sites.…”
Section: Stronger Rescue Of Telencephalon Patterning In Pax6mentioning
confidence: 99%
“…Interestingly, all of these genes, except NeuroD, genetically require Pax6 (Marquardt et al, 2001;Blader et al, 2004). The activation of Ngn1 and Ngn2 is directly regulated by Pax6 binding to particular CNS enhancers (Marquardt et al, 2001;Scardigli et al, 2003;Blader et al, 2004).…”
Section: Regulatory Conservation In the Evolutionary Divergence Of Bhmentioning
confidence: 99%
“…It is well known that PAX6 influences development of the nervous system and brain through regulation of proneural genes such as neurogenin 2 (Ngn2) and achaete-scute complex homolog-like 1 (Mash-1) (van Heyningen and Williamson 2002;Scardigli et al (2003). In human populations, recent studies have identified individuals with PAX6 mutations who present only with mental retardation and aniridia (Malandrini et al 2001;Ticho et al (2006;Graziano et al (2007).…”
Section: Introductionmentioning
confidence: 99%